Determinants of MSME Competitiveness: A Quantitative SEM-PLS Analysis of Total Quality Management - Siregar, Dina Arfianti; Nizma, Cut; Nofianna, Siti Asnida; Ismail (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This research addresses low competitiveness in the halal culinary creative industry caused by weak quality management implementation and a lack of business innovation, making improved product quality and managerial efficiency urgent for survival amid global competition. The purpose is to develop a contextual total quality management model based on local conditions to enhance enterprise competitiveness in the creative industry. The method employed a quantitative approach using Structural Equation Modeling – Partial Least Squares, with 100 halal culinary business owners selected purposively. The questionnaire was based on seven Malcolm Baldrige National Quality Award criteria: leadership, strategic planning, customer focus, human resource focus, process management, business results, and competitiveness. Data was collected through surveys and interviews, and analyzed using SmartPLS 4.0. Findings reveal that customer focus, business results, and process management significantly influence competitiveness with probability values below 0.05, indicating that enhanced customer orientation, business effectiveness, and process management strengthen competitiveness. The conclusion is that this research produces a contextual total quality management model, enriching quality management literature based on the Indonesian local context. Practically, this model provides actionable guidance for business owners to prioritize customer orientation, optimize operational processes, and measure performance systematically to improve their competitive position in the market.